The Dialectal Provenance of London, Wellcome Library, Ms 5262 - Esteban-Segura, Laura (Studia Anglica Posnaniensia, 2015)
This paper takes into consideration the language found in London, Wellcome Library, MS 5262, a one-volume codex from the early fifteenth century which holds a medical recipe collection. The manuscript, written in Middle English (and with a few fragments in Latin), represents a fine exemplar of a remedybook, a type of writing that has been traditionally considered to be popular. The main aim is to study the dialect of the text contained in folios 3v-61v in order to localise it geographically. The methodology followed for the purpose is grounded on the model supplied by the Linguistic Atlas of Late Mediaeval English (LALME) (McIntosh et al. 1986), which consists of several stages including the completion of a survey questionnaire, the creation of the linguistic profile of the text and the application of the ‘fit’-technique (McIntosh et al. 1986, vol. 1: 10-12; Benskin 1991). Extralinguistic features of the manuscript may also be taken into consideration. This comprehensive analysis will help us to circumscribe the dialectal provenance and/or local origin of the text accurately.